A new regional agreement for Latin america and the Caribbean on River principle 10 - Escazú Agreement - Ipenza Peralta, César A. (2018)
This article deals with the process of subscription and subsequent ratification of the Regional Agreement on Access to Information, Public Participation and Access to Justice in Environmental Matters in Latin America and the Caribbean or the Escazú Agreement. It is an international instrument to prevent socio-environmental conflicts because it allows increasing the measures aimed at accessing information and generating mechanisms that guarantee a new way of improving decision-making in the States.